When the state meets the street: public service and moral agency - Zacka, Bernardo (The Belknap Press of Harvard University Press, 2017)
'When the State Meets the Street' probes the complex moral lives of street-level bureaucrats: the frontline social and welfare workers, police officers, and educators who represent government's human face to ordinary citizens. Too often dismissed as soulless operators, these workers wield a significant margin of discretion and make decisions that considerably affect people's lives. By combining insights from political theory with ethnographic fieldwork as a receptionist in an urban anti-poverty agency, Bernardo Zacka shows us firsthand the predicament in which these public servants are caught up. Public policy consists of rules and regulations, but its implementation depends on how street-level bureaucrats interpret them and exercise discretionary judgment. These workers are expected to act as sensible moral agents in a working environment that is notoriously challenging and that conspires against them. Pressed to cope with the pressures of everyday work, they often and unknowingly settle for reductive conceptions of their responsibilities. Zacka examines the factors that contribute to this erosion of moral sensibility and what it takes to remain a balanced moral agent in such adverse conditions.--